The impact of cryoprotectant exposure time on post-thaw viability of autologous and allogeneic hematopoietic stem cells and leukocyte subpopulations - Rimac Vladimira; Bojanić Ines; Dabelić Sanja; Ćepulić Branka Golubić (Acta Pharmaceutica)
Although the use of cryoprotectant dimethyl sulfoxide (DMSO) is the gold standard in cryopreservation of hematopoietic stem cells, it is well known that it has a negative effect on cell viability. The aim of this prospective study was to examine how the length of post-thaw exposure to DMSO affects the cell viability and stability of peripheral blood stem cell (PBSC) samples. Additionally, the effects of donor type and pre-cryopreservation storage time on post-thaw viability during the stability study were evaluated. In 30 autologous and 30 allogeneic PBSC samples viable CD34+, CD14+, CD19+, CD16+/56+, and CD3+ cells were determined immediately after thawing, and one-and three-hours post-thaw.